Bumping Objects Together as a Semantically Rich Way of Forming Connections between Ubiquitous Devices - Hinckley, Ken (2003)
This research explores the use of distributed sensors to form dedicated and semantically rich connections between devices. For example, by physically bumping together the displays of multiple tablet computers that are facing the same way, dynamic display tiling allows users to create a temporary larger display. If two users facing one another instead bump the tops of their tablets together, this creates a collaborative face-to-face workspace with a shared whiteboard application. Each tablet is augmented with sensors including a two-axis linear accelerometer, which provides sufficient information to determine the relationship between the two devices when they collide.